Online education in Uzbekistan - Umarova, Saodat; Kudratova, Zebo (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The learning process is the interaction of the teacher, student and learning tools. The capabilities of modern computer tools andinformation technologies make it possible to assign part of the teacher’s functions and part of the learner’s functions adopted in the classical form of training to teaching aids. The COVID-19 pandemic affected most countries of the world and almost all spheres of public life, and the education system was no exception. One of the ways to contain coronavirus infection is still social exclusion; its measures required the partial or complete closure of educational institutions and the associated infrastructure